Kontribusi Variasi Latihan Bola Tangan terhadap Kemampuan Daya Tahan Vo2Max Mahasiswa - Ishaq Gery, Muhammad; Mujtaba, Imam; Setiyaningsih, Dewi; Alhaqiqi, Aditya; Mahfud, Imam (LPPM UNIVERSITAS MUHAMMADIYAH MUARA BUNGO, 2025)
One of the movement activities in sports is like a handball game. Handball is a fast and precise sport. Players and the ball move quickly and accurately. The handball coaching team at the sports education study program at University of Jakarta was evaluated. The team's productivity was very low in each match. It is also necessary to evaluate the training program to ensure it is arranged properly. Researchers on the team found that to keep up with the game's rhythm and intensity, it's important to increase the player's VO2max, or endurance. The research design used was a one-group pre-test-post-test design. Researchers found that the type of training had a big effect on increasing VO2 Max. On average, there was a 3-level increase from the test before the training to the test after the training. The t-test results show that the training variations have a sig. t test value of 0.000, which is less < 0.05. This means that the hypothesis is true: